LEXICAL FEATURES OF FINANCIAL TERMINOLOGY IN ENGLISH AND UZBEK - Maxmudov Jamol (TADQIQOTLAR, 2025)
Abstract This article explores the lexical features of financial terminology in English and Uzbek. It focuses on the structure, origin, and semantic characteristics of financial terms in both languages, highlighting similarities and differences shaped by linguistic, cultural, and economic contexts.